Effect of Organizational Structure, Job Analysis and Leadership Style on Work Motivation and Its Impact on Performance of Employees - Andhi Sukma Hanafi (Brawijaya University, 2019)
The purpose of this research is to: 1) Influence of organizational structure, job analysis, and leadership style on work motivation, 2) Influence of organizational structure, job analysis, and leadership style on employee performance, 3) Influence of work motivation on employee performance. This study was conducted at SMK SMTI in Indonesia with 183 employees as respondents. This research uses SEM AMOS for data analysis. The study found that organizational structure, job analysis, and leadership style significantly influenced work motivation, while the organizational structure is the highest variable influenced on work motivation with the value of influence of 0,608. Organizational structure, job analysis, and leadership style significantly influenced the employee performance, while the leadership style variable is the highest variable influence on the performance of employees with the value of influence of 0,946. In addition, work motivation has significantly affected employee performance with an influence value of 0,384.